Do Inclusive Education Policies Improve Employment Opportunities? Evidence from a Field Experiment - Jorge M. Agüero; Francisco Galarza; Gustavo Yamada (Institute of Labor Economics (IZA), 2020)
In labor markets where disadvantaged students are discriminated against, meritbased college scholarships targeting these students could convey two opposing signals to employers. There is a positive signal reflecting the candidate's cognitive ability (talented in high-school and able to maintain a high GPA in college) as well as her soft skills (overcoming poverty). There is also a possible negative signal as the targeting of the scholarship indicates that the beneficiary comes from a disadvantaged household. We conduct a correspondence study to analyze the labor market impact of an inclusive education program. Beca 18 provides merit-based scholarships to talented poor students admitted to 3-year and 5-year colleges in Peru. We find that the positive signal dominates. Including information of being a scholarship recipient increases the likelihood of getting a callback for a job interview by 20%. However, the effect is much smaller in jobs and careers where the poor are under-represented, suggesting that the negative signal of the scholarship is not zero.
Keywords: C93; I23; J7; J15; 330; employment; inclusive education; correspondence study; discrimination